The ethnoecology of the Malay sacred myth through narratives of Kampung Tua Nongsa in Batam - Tomi Arianto; Adrias Adrias; Septriani Septriani; Febri Yulika (Studies in English Language and Education, 2024)
The condition of the Malays is significantly marginalized due to the migration and the rapid industrial development in Batam, Indonesia. However, the Malay sacred myth is still sustained as a local wisdom for the Malay generations. Therefore, this study aims to analyze the ethnoecology behind the story of the sacred myth of Bumbum, Puak, and Batu Belah as a representation of environmental Malay local wisdom in Kampong Tua Nongsa, Batam. Within the conceptual framework of ethnoecology as a bridge to understanding the relationship between literature in the form of folklore and the culture of society, this qualitative research collected data through observation by being directly involved in the community and in-depth interviews with 21 informants including the key jury of the sacred places, community advice, community leaders, village officials, and the younger generation of Malay people in Kampong Tua Nongsa. Data analysis was carried out by comparing, reconfirming, classifying, and interpreting the data with an ethnoecology approach. The results showed that there were three important ethnoecological representations: (1) the ecological ties between forests and humans in the sacred Bumbum, (2) the reflection of the wise king in the sacred of Puak, and (3) the sea as the central life of nature in the sacred of Batu Belah. Sacred site prohibitions reveal deep connections between human behavior and nature, emphasizing ethical considerations; these stories highlight cultural values, insights for heritage preservation, and solutions for environmental challenges within an ethnoecological framework, stressing the importance of ethics in human-nature interactions.